Enhancement of Heat Dissipation in Ultraviolet Light‐Emitting Diodes by a Vertically Oriented Graphene Nanowall Buffer Layer. Issue 29 (29th May 2019) - Ci, Haina; Chang, Hongliang; Wang, Ruoyu; Wei, Tongbo; Wang, Yunyu; Chen, Zhaolong; Sun, Yuanwei; Dou, Zhipeng; Liu, Zhiqiang; Li, Jinmin; Gao, Peng; Liu, Zhongfan
Abstract: For III‐nitride‐based devices, such as high‐brightness light‐emitting diodes (LEDs), the poor heat dissipation of the sapphire substrate is deleterious to the energy efficiency and restricts many of their applications. Herein, the role of vertically oriented graphene (VG) nanowalls as a buffer layer for improving the heat dissipation in AlN films on sapphire substrates is studied. It is found that VG nanowalls can effectively enhance the heat dissipation between an AlN film and a sapphire substrate in the longitudinal direction because of their unique vertical structure and good thermal conductivity. Thus, an LED fabricated on a VG‐sapphire substrate shows a 37% improved light output power under a high injection current (350 mA) with an effective 3.8% temperature reduction. Moreover, the introduction of VG nanowalls does not degrade the quality of the AlN film, but instead promotes AlN nucleation and significantly reduces the epilayer strain that is generated during the cooling process. These findings suggest that the VG nanowalls can be a good buffer layer candidate in III‐nitride semiconductor devices, especially for improving the heat dissipation in high‐brightness LEDs. Abstract : The use of vertically oriented graphene (VG) nanowalls as a buffer layer for the growth of single‐crystal AlN film on a sapphire substrate to improve heat dissipation is proposed. Thus, a light‐emitting diode fabricated on a VG‐sapphire substrate shows a 37% improved light output power under a high injection current (350 mA) with an effective 3.8% temperature reduction.